Perencanaan Strategis dalam Pengembangan Desa Wisata di Kabupaten Bandung (Suatu Kajian di Kecamatan Ciwidey) - Maman Suherman AR (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine the Strategic Planning carried out by the Bandung Regency Tourism and Culture Office in the development of Tourism Villages in Ciwidey District. The method used in this research study is descriptive analysis with a qualitative approach. Researchers used a strategic planning model with data analysis using SWOT analysis, while the data collection techniques used in this study were library/documentation studies, observations, and interviews. The initial step taken was to analyze the internal and external environment to determine strengths, weaknesses, opportunities and threats in the development of Tourism Villages in Ciwidey District. After that the researcher also analyzes the issues that arise and looks at strategic issues. From this analysis there are several very strategic issues, namely the issue of increasing cooperation with related parties, the issue of increasing promotion to attract more tourists and the issue of seeking to allocate funds for natural disaster management, the issue of providing professional guides and the issue of provide outreach and guidance to the community visiting the Tourism Village in Ciwidey District. Whereas in strategic planning for the development of a Tourism Village in Ciwidey District there are several weaknesses, namely limited professional human resources, limited available funds and lack of optimal promotion. For this reason, the suggestions made to overcome these weaknesses include: to overcome the limitations of professional human resources, the government needs to recruit employees who have an educational background in tourism. To address strategic issues related to promotion, the Bandung Regency Tourism and Culture Office should optimally activate websites, social media, and applications and explain in detail the more attractiveness that Tourism Villages have in Ciwidey District and programs under development. Tourism Village in Ciwidey District.